Field notes contributed by James J. Dinsmore, spring 1983 - Dinsmore, James J.et al (1983)
Spring report of birds contributed by James J. Dinsmore. A note about a dead Barn Owl found near Ottumwa is included. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1983. Epson - sheet feed